Slow Tourism Concept: Strategies in Improving Tourism in Indonesia - Ainil Mardiah; Nyoman Gede Mas Wiartha; I Made Sucipta Adnyana; A.A Istri M. Septiviari; I Gst Made Iwan Dusanta (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research is a qualitative research with a descriptive approach. The data used in this article are secondary data that researchers obtained from various credible scientific sources and were analyzed with the stages of data collection, data selection, data reduction, and drawing conclusions. The result in this article show that Pesona Indonesia and Slow Tourism Concept have contrasting differences but can be collaborated. As is the case, regarding Pesona Indonesia, it focuses more on the target visitors in terms of quantity while Slow Tourism Concept focuses more on quality. If collaborated, the focus can change to quantity and quality where visitors are in large numbers and get education about nature, good relations between visitors, and good relations between local residents. In addition, the experience gained by visitors will be more pronounced if they get a beautiful tourist spot according to the Pesona Indonesia concept if accompanied by valuable experiences from the Slow Tourism concept. Thus, researchers are increasingly convinced that the presence of the Slow Tourism Concept collaborated with the Pesona Indonesia Concept can further increase tourism in Indonesia.